Foucault y Guibert, la palabra y el silencio. - Fernández Agis, Domingo (Análisis. Revista de investigación filosófica, 2017)
Cuando Hervé Guibert habla de su relación con Michel Foucault, en las páginas de sus novelas, A l’ami qui ne m’a pas sauvé la vie y Le protocole compassionnel, está narrando la verdad de su experiencia, la verdad de Foucault como él la ha conocido. Es innegable que esta verdad no es la verdad del mismo Foucault. Guibert narra aquello que, sin condenar a Foucault, puede facilitarle a él mismo su absolución. Ciertos detalles son quizá bastante crueles, pero nos hacen pensar en la relación muy particular que Foucault ha mantenido con su rica herencia intelectual. Los recelos del filósofo hacia el futuro de su obra nos dicen que era muy consciente del valor de sus contribuciones al pensamiento contemporáneo. Después de haber reflexionado sobre sus vidas y sus obras, se comprende que el compromiso apasionado con la escritura de estas dos personalidades tan creativas, tiene tanta importancia como su compromiso con la vida. TITLE: Foucault, Guibert , the speech and the silence ABSTRACT: When Hervé Guibert talks about his relationship with Michel Foucault, in the pages of his novels, A l’ami qui ne m’a pas sauvé la vie and Le protocole compassionnel, he is telling the truth of their experience, the truth of Foucault as he has known it. It is undeniable that this truth is not Foucault’s truth. Guibert tells only that which, without condemning Foucault, can provide his acquittal. Certain details are perhaps rather cruel, but they make us think of the very special relationship that Foucault had with its rich intellectual heritage. The philosopher’s misgivings about the future of his work tell us that he was well aware of the value of their contribution to contemporary thought. He has always wanted to underline its willingness to produce new guidelines to thinking, and he has succeeded. Therefore, he does not want the fruits of their labour from being betrayed, however good the intentions were that they did. After reflecting on their lives and works, it is understood that the passionate commitment of these two very reative characters with their writing, is as important as their commitment to life.